The HFE p.H63D (p.His63Asp) Polymorphism Is a Modifier of ALS Outcome in Italian and French Patients with SOD1 Mutations - Antonio Canosa; Andrea Calvo; Gabriele Mora; Cristina Moglia; Maura Brunetti; Marco Barberis; Giuseppe Borghero; Claudia Caponnetto; Francesca Trojsi; Rossella Spataro; Paolo Volanti; Isabella Laura Simone; et al. (Biomedicines, 2023)
Background: Data from published studies about the effect of HFE polymorphisms on ALS risk, phenotype, and survival are still inconclusive. We aimed at evaluating whether the p.H63D polymorphism is a modifier of phenotype and survival in SOD1-mutated patients. Methods: We included 183 SOD1-mutated ALS patients. Mutations were classified as severe or mild according to the median survival of the study population. Patients were screened for the HFE p.H63D polymorphism. Survival was calculated using the Kaplan–Meier modeling, and differences were measured by the log-rank test. Multivariable analysis was performed with the Cox proportional hazards model (stepwise backward). Results: SOD1 severe mutation carriers show more frequent familial history for ALS and shorter survival compared to mild mutation carriers. Carriers and non-carriers of the p.H63D polymorphism did not differ in terms of sex ratio, frequency of positive familial history, age at onset, and bulbar/spinal ratio. In univariate and in Cox multivariable analysis using sex, age at onset, site of onset, family history, country of origin, and mutation severity as covariates, p.H63D carriers had a longer survival (p = 0.034 and p = 0.004). Conclusions: We found that SOD1-mutated ALS patients carrying the p.H63D HFE polymorphism have a longer survival compared to non-carriers, independently of sex, age and site of onset, family history, nation of origin, and severity of mutations, suggesting a possible role as disease progression modifier for the p.H63D HFE polymorphism in SOD1-ALS.